2011
DOI: 10.1007/s13593-011-0005-5
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the nitrogen management strategy using an optical sensor for irrigated wheat

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(39 citation statements)
references
References 25 publications
(38 reference statements)
2
37
0
Order By: Relevance
“…This nondestructive methodology using active sensors, that can be used day or night, is commercially available and has delivered increased profits for wheat and maize producers (Scharf et al, 2011). Added studies have used algorithms that employ mid-season sensor readings for predicting yield potential and via well-defined algorithms have resulted in refined fertilizer N rates (Bushong et al, 2016;Singh et al, 2011;Solie et al, 2012;Crain et al, 2012). This methodology has also resulted in more accurate prediction of agronomic optimum N rates compared to yield goal/soil test based methods.…”
Section: Discussionmentioning
confidence: 99%
“…This nondestructive methodology using active sensors, that can be used day or night, is commercially available and has delivered increased profits for wheat and maize producers (Scharf et al, 2011). Added studies have used algorithms that employ mid-season sensor readings for predicting yield potential and via well-defined algorithms have resulted in refined fertilizer N rates (Bushong et al, 2016;Singh et al, 2011;Solie et al, 2012;Crain et al, 2012). This methodology has also resulted in more accurate prediction of agronomic optimum N rates compared to yield goal/soil test based methods.…”
Section: Discussionmentioning
confidence: 99%
“…In the plots with RDN, the total amount P and K and 33% of N was applied as basal dose at the time of seeding/transplanting and the remaining two-third of N was applied in two equal splits at 20-25 and 40-45 days after seeding/transplanting in rice and wheat. In the plots with 80% RDN + GS, total amount P and K along with 80% of RDN was applied as basal dose at the time of seeding/transplanting and the remaining N was applied as guided by the GS optical sensor using a standard calibration curve (Bijay-Singh et al 2011).…”
Section: Crop Managementmentioning
confidence: 99%
“…Nitrogen uptake of irrigated wheat proceeds very slowly until tillering begins, and N flux (kg N ha -1 day -1 ) increases to a maximum around Feekes six stage [7], which coincides with maximum tillering stage at second irrigation. BijaySingh et al [5] observed that high N use efficiency in irrigated wheat can be achieved by applying moderate amount of fertilizer N at planting and MT stages and sensor-guided fertilizer N dose at Feekes 5-6 or 7-8 stages of wheat.…”
Section: Resultsmentioning
confidence: 99%
“…The SPAD meter measurements at Zadok stages 37-41 (maximum number of florets per ear primordium) and Zadok stages 52-58 (pollen grains on well-developed stigmatic hairs) were useful in identifying wheat cultivars responsive or non-responsive to N application. Some recent studies on wheat [4,5,25] grown in the IGP have shown that a dose of fertilizer N needs to be applied at MT stage as per need of the crop to achieve high fertilizer N use efficiency. However, the criteria to decide application of fertilizer N dose were coupled with a well-defined fertilizer N management schedule at planting and at CRI stages.…”
Section: Resultsmentioning
confidence: 99%